The Role of The Uzbek Language in The Process of Globalization In The World Arena (Eurasian Journal of Humanities and Social Sciences, 2024)
Uzbek is one of the 100 languages in the world with the status of a state language. However, there are also languages in the world that do not have such a high status, but are spoken by hundreds of millions.